2003
DOI: 10.1519/1533-4287(2003)017<0140:pamsrd>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Power and Maximum Strength Relationships During Performance of Dynamic and Static Weighted Jumps

Abstract: The purpose of this study was to investigate the relationship of the 1 repetition maximum (1RM) squat to power output during countermovement and static weighted vertical squat jumps. The training experience of subjects (N = 22, 87.0 +/- 15.3 kg, 14.1 +/- 7.1% fat, 22.2 +/- 3.8 years) ranged from 7 weeks to 15+ years. Based on the 1RM squat, subjects were further divided into the 5 strongest and 5 weakest subjects (p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
135
3
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(150 citation statements)
references
References 20 publications
9
135
3
3
Order By: Relevance
“…Weighted jumps are likely to be effective exercises for developing power based on a number of factors. In the scientific literature peak power values as large as 4750 to 6250 W (≈ 45 to 70 W/kg) have been reported for male athletes performing the SBJ (5,9,36). In addition, research comparing exercises used frequently by athletes to develop lower-body power (squat, power clean and SBJ) demonstrated that the SBJ produced the largest power values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weighted jumps are likely to be effective exercises for developing power based on a number of factors. In the scientific literature peak power values as large as 4750 to 6250 W (≈ 45 to 70 W/kg) have been reported for male athletes performing the SBJ (5,9,36). In addition, research comparing exercises used frequently by athletes to develop lower-body power (squat, power clean and SBJ) demonstrated that the SBJ produced the largest power values.…”
Section: Discussionmentioning
confidence: 99%
“…The jump squat has been used extensively by researchers to investigate the load-power relationship (4,5,9,13,35,36,38). The rationale for the extensive study is the thesis that the load which maximises power provides the most effective stimulus for power development (4) Initial results from studies investigating the load-power relationship with the jump squat reported that power was maximized with loads of 30 to 60% 1RM (4,35,36,38). However, more recent studies have consistently shown that power is maximized when vertical jumps are performed unloaded (5,8,9,13).…”
Section: Introductionmentioning
confidence: 99%
“…The problem is the procedure for assessment, ie Cormie et al 18 measured the peak power and in our study we measured average power, so it becomes more difficult to make comparisons between studies. By contrast, Stone et al 12 recorded that the optimum load to achieve maximum power in squat jump and CMJ EL was 10% RM, but keep in mind that in this work the lowest charge made was this. Another study by Harris et al 26 found that the maximum power for both the peak power (PP) and for average power (P avg ) was attained with loads of 21.6 ± 7.1% and 39.0 ± 8.6% of the RM in the squat, respectively.…”
Section: Discussionmentioning
confidence: 61%
“…According to Stone et al 12 maximum strength is related to power production and that increases in maximum strength may lead to an increased in power production. One possible explanation may be due to the increase of maximum strength at a given absolute load that may represent a relative load (% RM) lower, so that as the work of Gonzalez-Badillo et al 1 this lower percentage can be shifted at a higher speed, with a subsequent increase in power for this load.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation